"Don't Be Shy to Ask for Help": Group Work With Urban, Black, First-Generation College Students. (2nd October 2022) - Malott, Krista M.; Gosai, Shivam; Khan, Zara; Precourt, Katherine; Gamerman, Tracy; Waldman, Genevieve
Abstract : An urban, Black high school population share their experiences of a college preparatory counseling group specific to prospective first-generation college students (PFGCS). The salience of help seeking, as a major theme in this study, is highlighted and explored according to Black, first-generation college going students. Participant experiences include aspects of limited knowledge in regard to preparing for, and navigating, college, as well barriers to help-seeking influenced by gender socialization and racism. Participant experiences suggest affinity group work as a means for addressing such barriers.